The Effectiveness of Learning Model of Contextual Writing Poetry Based on Literary Ecology - Nori Anggraini; Nurudin Nurudin; Saefur Rohman (Journal of English Education and Teaching, 2022)
This research aims to describe the effectiveness of contextual learning models of creative writing based on the literary ecology of Indonesian Language and Literature Study (PBSI) students at Education Faculty (FKIP) Muhammadiyah University of Tangerang. The research method used in this research is Research and Development (R&D). The population in this study were all students of the Indonesian Language and Literature Education Study Program in Academic Year 2020/2021 of semester VII who have taken Creative Writing courses while the sample in this study were 20 students of the Indonesian Language and Literature Education Study Program of Muhammadiyah University of Tangerang. The results of this study showed that after pre-test and post-test trials in creative writing courses based on literary ecology in PBSI students at FKIP Muhammadiyah University of Tangerang the learning model used had positive results and had a significant increase the students’ poetry writing skills. This can be seen in the results of the pretest signification test obtained an average of 3.5 and post-test results obtained an average of 7.05. Therefore, researchers can conclude that the learning model developed by researchers in creative writing courses based on literary ecology is feasible and effectively to be used. The learning model made was final and has fulfilled the requirements to be implemented in the classroom.